ALSUntangled #63: ketogenic diets. Issue 1 (2nd January 2023) - Bedlack, Richard; Barkhaus, Paul E.; Barnes, Benjamin; Beauchamp, Morgan; Bertorini, Tulio; Bromberg, Mark B.; Carter, Gregory T.; Chaudry, Vinay; Cudkowicz, Merit; Jackson, Ce; Levitsky, Gleb; Lund, Isaac; et al.
Abstract: ALSUntangled reviews alternative and off label treatments with a goal of helping patients make more informed decisions about them. Here we review ketogenic diets. We shows that these have plausible mechanisms, including augmenting cellular energy balance and reducing excitotoxicity, neuroinflammation and oxidative stress. We review a mouse model study, anecdotal reports and trials in ALS and other diseases. We conclude that there is yet not enough data to recommend ketogenic diets for patients with ALS, especially in light of the many side effects these can have.